2002
DOI: 10.1063/1.1507837
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies of L10 FePt nanoparticles

Abstract: We have studied the lattice parameter changes of L10 FePt nanoparticles annealed to near equilibrium as a function of composition by x-ray diffraction. We have found that the (111) diffraction peak shifts linearly with composition, however, the c parameter mostly changes in the Pt rich compositions and the a parameter mostly changes in the Fe rich compositions with respect to the equiatomic composition. This causes the tetragonality of the L10 structure to be maximized near the Fe 50%/Pt 50% composition. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
88
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(104 citation statements)
references
References 3 publications
13
88
0
Order By: Relevance
“…1, 3 Recently, there has been much attention placed on the chemical synthesis of self-assembled, monodispersed, and chemically ordered L1 0 ͑tetragonal phase͒ FePt nanoparticles for future ultrahigh-density magnetic storage. [4][5][6][7][8] In fact, recent advances in magnetic recording technology have indicated that, if self-assembled in a tightly packed, exchangedecoupled array with controlled magnetic easy axis direction, these FePt nanoparticles could support high-density magnetization reversal transitions and would be a candidate for future ultrahigh-density data storage media [8][9][10] with potentially one bit per particle corresponding to storage densities of 20 Tbit/ in. 2 The tetragonal phase of an FePt system is of particular interest because of the high magnetocrystalline anisotropy ͓K U ϳ͑6.6− 10͒ ϫ 10 7 erg/ cm 3 ͔ that should allow the use of smaller particles, but yet avoid thermal instabilities that give rise to superparamagnetic ͑SPM͒ behavior.…”
Section: Introductionmentioning
confidence: 99%
“…1, 3 Recently, there has been much attention placed on the chemical synthesis of self-assembled, monodispersed, and chemically ordered L1 0 ͑tetragonal phase͒ FePt nanoparticles for future ultrahigh-density magnetic storage. [4][5][6][7][8] In fact, recent advances in magnetic recording technology have indicated that, if self-assembled in a tightly packed, exchangedecoupled array with controlled magnetic easy axis direction, these FePt nanoparticles could support high-density magnetization reversal transitions and would be a candidate for future ultrahigh-density data storage media [8][9][10] with potentially one bit per particle corresponding to storage densities of 20 Tbit/ in. 2 The tetragonal phase of an FePt system is of particular interest because of the high magnetocrystalline anisotropy ͓K U ϳ͑6.6− 10͒ ϫ 10 7 erg/ cm 3 ͔ that should allow the use of smaller particles, but yet avoid thermal instabilities that give rise to superparamagnetic ͑SPM͒ behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, AF domains have highly minimized dipolar magnetic interaction between the neighboring bits, and could play a crucial role in reducing the density of the current magnetic storage device 49 . Additionally such AF multilayers can be an integral part of an exchange biased system and could have significant impact in the quest of ultra-fast magnetic switching 55,56 .…”
Section: Analysis and Discussion Of The Resultsmentioning
confidence: 99%
“…It is also worthwhile to investigate the impact of Na ions on the magnetic anisotropy energy (MAE) which determines the stability of magnetic systems. In this regard materials with FePt composition are known to have high MAE 14,47,48 and are used for the current high density recording media 49 . Here, we show that MAE of FePt multilayer can be further enhanced by adsorption of Na ions.…”
Section: Magnetic Hardening Of Fept Multilayers With Na Ionsmentioning
confidence: 99%
“…Since the atomic ordering was promoted with the increase of substrate temperature, the degree of atomic order was considered to be very low in the case of specimens deposited at the substrate temperatures of 563 and 583 K. By contrast, the atomic ordering for the specimen deposited at 613 K was much promoted and, simultaneously, the coercivity was also increased with the decrease of axial ratio c=a as shown in the later section 3. ) or FePt nanoparticles (c=a ¼ 0:961, 19) c=a ¼ 0:966 26) ). Here S denotes the LRO parameter.…”
Section: à2mentioning
confidence: 99%